1987
DOI: 10.1287/mnsc.33.9.1102
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Group Formation and Performance: The Case of the U.S. Pharmaceutical Industry, 1963–1982

Abstract: The focus of this paper is on three major questions: (1) what is the theoretical rationale for the strategic group concept?; (2) does strategic group membership have performance implications?; and (3) are strategic groups and membership in strategic groups stable characteristics of industries? A statistical procedure is proposed to longitudinally identify strategic groups. The empirical setting is the U.S. pharmaceutical industry over the period 1963–82. While performance differences are found in terms of mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
423
3
48

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(489 citation statements)
references
References 23 publications
15
423
3
48
Order By: Relevance
“…To avoid the limitations of regression analysis for studying configurations, in a considerable number of studies, researchers have instead employed cluster analysis (e.g., Bensaou & Venkatraman, 1995;Cool & Schendel, 1987;Desarbo, Di Benedetto, Song, & Sinha, 2005;Dess & Davis, 1984;Ferguson, Deephouse, & Ferguson, 2000;Fiegenbaum & Thomas, 1990;Hambrick, 1983;Ketchen et al, 1993;Lim, Acito, & Rusetski, 2006;Moores & Yuen, 2001). Typically, these studies use clustering algorithms to identify distinct groups of firms and then employ ANOVA or MANOVA to examine whether the distinct groups show differences in their performance.…”
Section: The Mismatch Between Configurational Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the limitations of regression analysis for studying configurations, in a considerable number of studies, researchers have instead employed cluster analysis (e.g., Bensaou & Venkatraman, 1995;Cool & Schendel, 1987;Desarbo, Di Benedetto, Song, & Sinha, 2005;Dess & Davis, 1984;Ferguson, Deephouse, & Ferguson, 2000;Fiegenbaum & Thomas, 1990;Hambrick, 1983;Ketchen et al, 1993;Lim, Acito, & Rusetski, 2006;Moores & Yuen, 2001). Typically, these studies use clustering algorithms to identify distinct groups of firms and then employ ANOVA or MANOVA to examine whether the distinct groups show differences in their performance.…”
Section: The Mismatch Between Configurational Theory and Methodsmentioning
confidence: 99%
“…To establish and measure configuration membership, authors have used a variety of clustering algorithms (e.g., Bensaou & Venkatraman, 1995;Cool & Schendel, 1987;Fiegenbaum & Thomas, 1990;Hambrick, 1983;Ketchen et al, 1993), interaction effects (e.g., Baker & Cullen, 1993;Dess, Lumpkin, & Covin, 1997), and deviation score approaches (e.g., Delery & Doty, 1996; to identify configurations and their effects, typically on performance as the key outcome variable. However, evidence on the relationship between configurations and performance has been equivocal.…”
mentioning
confidence: 99%
“…Eggers and Kaplan (2009) complemented this finding by establishing that managerial attention timing is important for explaining the speed of asset reconfiguration. Several scholars further demonstrated that cognition precedes asset reconfiguration-that is, managerial attention leads to strategic change, as shown in studies that seek to mitigate simultaneous and reverse causality, and rule out alternative explanations (Cho & Hambrick, 2006;Cool & Schendel, 1987;Kaplan, Murray, & Henderson, 2003). At the industry level, cognition scholars found that competitors endowed with similar assets can respond very differently to the same environmental shift when their top managers' attentional patterns differ (Fiol, 1990;Osborne, Stubbart, & Ramaprasad, 2001;Porac & Thomas, 1994).…”
Section: Cognition and Firm Response: The Role Of Managerial Attentionmentioning
confidence: 99%
“…To that end, most researchers found significant differences in financial results between groups identified, us ing cluster analysis (Dess andDavid, 1984: Reger andHuff, 1993;Heene and Houthoofd, 2002). Some of the authors, however, did not detect significant differences in profitabilities that could be explained by allocation to par ticular groups (Frazier and Howell, 1983;Cool and Schendel, 1987;Martens, 1988). Nevertheless, papers that analysed the banking sectors generally identified significant differences between groups in terms of prof itability (Mehra, 1996;Koller, 2001).…”
Section: Review Of Empirical Researchmentioning
confidence: 98%